THE EXPLOSIVE POWER OF THE ARMS AND LEGS AND THEIR RELATIONSHIP TO THE ACCURACY OF THE SHOOTING SKILL BY JUMPING IN FRONT OF THE HANDBALL - Assistant Teacher. Doaa Alaa Manea (Galaxy International Interdisciplinary Research Journal, 2024)
Success in achieving an injury. The shooting skill is considered one of the most effective skills that lead to jumping forward with high efficiency and great self-confidence, as they are confident of winning. Performing the shooting skill by jumping forward with a handball requires that the performance of the skill be subject to a set of variables and mechanical characteristics for the skill to appear. In its correct and precise form, it shows the importance of research in knowing the relationship between the explosive power of the arms and legs in performing the shooting skill of Jumping forward with the handball and the research problem. Through the researcher’s observation of what is happening in university tournaments and some school tournaments, there is a weakness in the skill performance of the shooting skill of jumping forward with the handball. This weakness may be due to a lack of attention to the explosive power of the legs and arms, which is the basis for this skill. Since The skill of shooting forward with a handball depends on its performance on explosive power, and to find appropriate solutions, the researcher decided to identify the relationship between the explosive power of the legs and arms and the shooting skill of jumping forward with the handball. The research objectives were to identify the relationship between the explosive power of the legs and arms and the shooting skill of the research is to identify the relationship between the explosive power of the legs and arms and the shooting skill of jumping in front of the handball. The researcher used the descriptive approach to correlate the relationships between the study variables. As for the research community and its sample, the research community was determined intentionally, and they are the University of Dhi Qar team players in the College of Physical Education and Science. Sports University of Dhi Qar, which numbered 15 players, were all selected as the proportion of Al Ain was 100% from the original community. The most important conclusion was that there was a correlation between the explosive power of the arms and the accuracy of aiming from jumping in front of the handball.